High‐Performance Thermoelectricity in Nanostructured Earth‐Abundant Copper Sulfides Bulk Materials. Issue 16 (14th June 2016) - Ge, Zhen‐Hua; Liu, Xiaoye; Feng, Dan; Lin, Jingyang; He, Jiaqing
Abstract : Na x Cu9 S5 ( x = 0, 0.025, 0.05, 0.15, 0.25) nanopowders with an average size of 3 nm are prepared by ball milling and are then sintered with spark plasma. Due to the small size of the nanopowders, the bulk materials possess very fine grains after sintering. The highest ZT value is about 1.1 at 773 K and is obtained for Na0.05 Cu9 S5 sample that is nearly threefold higher than that of pristine Cu9 S5 and comparable to the modified PbS materials (ZT ≈ 1.2 at 923 K).